The Revista Minerva adopts the continuous publication model - Romero-Castro, Isidro Galileo; Vega, Saúl Antonio; Martínez-Aguilar, Ever Alexis; Sermeño-Chicas, José Miguel (Revista Minerva, 2025)
The Revista Minerva will switch to continuous publication. This model will allow manuscripts to be published once they have completed the editorial process, without waiting for the issue to be completed. It will be implemented starting in the second half of 2025, and the biannual frequency will be maintained.